Fourier transform mid infrared spectroscopy applications for monitoring the structural plasticity of plant cell walls - Largo-Gosens, Asier; Hernández-Altamirano, Mabel; García-Calvo, Laura; Alonso-Simón, Ana; Álvarez, Jesús; Acebes, José L. (Frontiers in Plant Science, 2014)
Fourier Transform Mid-Infrared (FT-MIR) spectroscopy has been extensively used as a potent, fast and non-destructive procedure for analyzing cell wall architectures, with the capacity to provide abundant information about their polymers, functional groups, and in muro entanglement. In conjunction with multivariate analyses, this method has proved to be a valuable tool for tracking alterations in cell walls. The present review examines recent progress in the use of FT-MIR spectroscopy to monitor cell wall changes occurring in muro as a result of various factors, such as growth and development processes, genetic modifications, exposition or habituation to cellulose biosynthesis inhibitors and responses to other abiotic or biotic stresses, as well as its biotechnological applications.